Can a Knowledge Sharing Platform without a Brand Community Platfrom contribute to the Brand Community Commitment? - Sumarlin, Antonius Widyatma; Soehadi, Agus W; Suharjo, Budi; Daryanto, Heny K (SBM ITB, 2013)
Consumunity theory offers a view in which consumers can co-create the value in-use of the brand. Given a platform, consumers share their tastes and buy preferences for the benefits of others adapting to their surrounding social values. Many brand literatures address the platform as a brand community, yet there has not been any attempt to separate between the values of the brand community and the utilized spaces of knowledge sharing platform (KSP) because both platforms have been assumed to be embedded together in one platform. The purpose of this quantitative research is to show that KSP by its distinct roles and functions other than the values of brand community can also contribute to the brand community commitment. A sample of 600 respondents was collected with accidental sampling method at three various brand community events in Bogor and Jakarta, namely Kecap Bango Mania, Bogasari Baking Center and Ibu dan Balita of Frisian Flags. The analytical method employed is structural equation analysis using structural equation modelling (SEM) as its tool to run the data. The result of this descriptive research shows that there is a good probability that brand community commitment can be influenced by the knowledge sharing platform alone. This finding should be beneficial to the brand producer to consider KSP as an alternative means to have their employees involved in its activity to maintain the moral values of the brand. Keywords: Knowledge Sharing Platform, Brand Community Commitment, Consumunity Theory, Consumer Culture Theory, Brand Community